Combination application of microbial agent and lime application improves soil nutrients and soil fungi community, producing good quality tobacco - Zhang, Jingtao; Li, Chao; Xia, Kai; Cheng, Kaikai; Guo, Shanhu; Pan, Wenzheng; Liu, Lingling; Wang, Ke; Wen, Li; Tang, Haiming (Frontiers in Microbiology, 2025)
Agent addition is increasingly recognized as a crucial strategy for improving soil health in tobacco cultivation. However, its impacts on soil microbial community and plant growth differ depending on soil conditions. In this study, tobacco soil was collected in Wu Ding County, Yunnan Province, under four distinct agent addition treatments, simply chemical fertilizer (T1), microbial agent + chemical fertilizer (T2), lime + chemical fertilizer (T3), and microbial agent + lime + chemical fertilizer (T4). Using the Illumina high-throughput sequencing platform and fungal ribosomal DNA internal transcribed spacer 1 to analyze the distribution characteristics of fungal communities in tobacco soil. Soil nutrient indicators (pH, SOC, TN and AP) were considerably higher in T4 than in T1. In comparison to T1, agent addition boosted the agronomic characteristics such as maximum leaf length, maximum leaf width, stem girth, and leaf number. T4 treatment facilitated the harmonization of chemical composition of tobacco leaves and greatly increased tobacco yield by 8.94% than T1. The application of T4 resulted in a reduction of fungal diversity. Ascomycota was the most dominant phylum across all soil and agent applications distinctly shifting the soil fungal community diversity. Furthermore, certain beneficial fungi were obviously accumulated, but the potentially pathogenic fungi were noticeably reduced or absent in T4. An explicit enrichment of saprotrophic fungi in T4 is predicated by the FUNGuild function. Soil nutrients were extremely significant and relevant in relation to the fungal community structure. In summary, we propose that T4 treatment could be an effective strategy to alleviate the continuous cropping barrier in tobacco cultivation since it eliminates soil acidity, improves soil nutrients, and modifies the soil microbial community structure, thereby improving the plant growth and increasing the yield of tobacco.